2012
DOI: 10.1103/physrevlett.108.117202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Frustration in a Quantum Spin Chain: The Case of LinaritePbCuSO4(OH)2

Abstract: We present a combined neutron diffraction and bulk thermodynamic study of the natural mineral linarite PbCuSO4(OH)2, this way establishing the nature of the ground-state magnetic order. An incommensurate magnetic ordering with a propagation vector k=(0,0.186,1/2) was found below T(N)=2.8 K in a zero magnetic field. The analysis of the neutron diffraction data yields an elliptical helical structure, where one component (0.638μ(B)) is in the monoclinic ac plane forming an angle with the a axis of 27(2)°, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
95
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 30 publications
12
95
1
Order By: Relevance
“…In such compounds it is frequently found that the spin exchange interactions between the Cu 2+ (S=1/2) ions are such that the next-nearest-neighbor (NNN) exchange is antiferromagnetic (AFM), the nearest-neighbor (NN) exchange is ferromagnetic (FM), and the NNN spin exchange is often considerably stronger than the NN spin exchange. Due to the inherent competition of the NN and NNN spin exchange interactions, the CuX 2 ribbon chains tend to develop unusual AFM incommensurate spiral spin structures [1][2][3][4][5][6][7][8][9] and sometimes concomitantly multiferroic behavior. [10][11][12][13] These CuX 2 ribbon chains are formed by linking CuX 4 basal-square-planes of axially elongated CuX 6 (X = O, Cl, Br,...) octahedra together via their trans-edges.…”
Section: Low Dimensional Magnetic Cumentioning
confidence: 99%
See 1 more Smart Citation
“…In such compounds it is frequently found that the spin exchange interactions between the Cu 2+ (S=1/2) ions are such that the next-nearest-neighbor (NNN) exchange is antiferromagnetic (AFM), the nearest-neighbor (NN) exchange is ferromagnetic (FM), and the NNN spin exchange is often considerably stronger than the NN spin exchange. Due to the inherent competition of the NN and NNN spin exchange interactions, the CuX 2 ribbon chains tend to develop unusual AFM incommensurate spiral spin structures [1][2][3][4][5][6][7][8][9] and sometimes concomitantly multiferroic behavior. [10][11][12][13] These CuX 2 ribbon chains are formed by linking CuX 4 basal-square-planes of axially elongated CuX 6 (X = O, Cl, Br,...) octahedra together via their trans-edges.…”
Section: Low Dimensional Magnetic Cumentioning
confidence: 99%
“…Some systems, such as Li 2 ZrCuO 4 and PbCuSO 4 (OH) 2 (linarite), prevent long-range FM ordering since they exhibit an AFM incommensurate spin-spiral structure along the ribbon chains. 8,9,19,20 Other systems, such as Ca 2 Y 2 Cu 5 O 10 and Li 2 CuO 2 , do contain FM ribbon chains, however, weak interchain interactions force the FM-ribbon chains to align antiparallel, resulting in long-range AFM ordering. [21][22][23][24][25][26] In the case of Li 2 CuO 2 , the absence of a spiral magnetic order in the ribbon chains is understood to be a consequence of order by disorder arising from interchain interactions.…”
Section: -18mentioning
confidence: 99%
“…Below T N = 2.8 K linarite shows magnetic long range order at zero field. Neutron scattering experiments 31 have confirmed the spin structure of the ground state to be an elliptical helix with the propagation vector k = (0, 0.186, 0.5). From bulk magnetic measurements, we have estimated the magnetic exchange interactions, with FM-NN J 1 ≈ −100 K, AFM-NNN J 2 ≈ 36 K and J ic ∼ 5 K 30 .…”
mentioning
confidence: 99%
“…Unfortunately, for many of the candidates for exhibiting multipolar phases, the involved AFM magnetic couplings and thus the saturation field are quite large, making it difficult to probe the multipolar phases. In this respect, linarite, PbCuSO 4 (OH) 2 , is a promising spin-multipolar candidate as the Cu 2+ ions form a quasi-1D S = 1/2 spinchain along the crystallographic b-axis 17,[30][31][32][33] . The material crystallizes in a monoclinic space group P 2 1 /m with lattice parameters 31,32,34 (at 1.8 K) a = 9.682Å, b = 5.646Å, c = 4.683Å, and β = 102.65 • (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation